2022
DOI: 10.1021/acs.jpcc.1c08675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Electronic Properties of the Ligand on the Photoelectrochemical Behavior of Au25 Nanocluster-Sensitized TiO2 Photoanode

Abstract: Atomically precise metal nanoclusters (NCs) have recently emerged as a new class of bifunctional (photoactive and catalytically active) photosensitizers in light energy conversion applications. Despite the size and alloy effects of NCs, no effort has been made to elucidate how the protecting ligand affects the photoelectrochemistry of the NC-sensitized photoelectrodes. With a nanoporous TiO2 array as model support, Au25 NCs protected by various thiol-bearing ligands have been used to prepare four different pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 46 publications
(83 reference statements)
0
16
0
Order By: Relevance
“…[13][14][15] The processes that might take place at the metal-semiconductor interface are complex. The character of the observed effect is determined by the type of metal (e.g., the junction type depends on the difference in the work functions of metal and TiO 2 ), but also more recently size-dependent behavior was found to be an important aspect to be considered (e.g., single atoms, 16 metal clusters, 17,18 nanoparticles 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] The processes that might take place at the metal-semiconductor interface are complex. The character of the observed effect is determined by the type of metal (e.g., the junction type depends on the difference in the work functions of metal and TiO 2 ), but also more recently size-dependent behavior was found to be an important aspect to be considered (e.g., single atoms, 16 metal clusters, 17,18 nanoparticles 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…, the junction type depends on the difference in the work functions of metal and TiO 2 ), but also more recently size-dependent behavior was found to be an important aspect to be considered ( e.g. , single atoms, 16 metal clusters, 17,18 nanoparticles 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic SR ligands are more effective in terms of improving PCE than aliphatic SR ligands (Figure 26E). [322] 6. The use of Au n (SC12) m NCs enhances the performance of organic solar cells based on PTB7:PC 70 BM Reproduced with permission: Copyright 2021, American Chemical Society.…”
Section: Energy and Environmental Materialsmentioning
confidence: 99%
“…As such, NCLs find application in catalysis, sensing, and optoelectronic devices. 33,39,[43][44][45][46] Owing to their small size of less than 3 nm, NCLs behave like molecules with electron transitions/excitonic states, unlike plasmonic nanoparticles, which exhibit surface plasmon resonances. 48 In 2008, Jin and co-workers reported the first study on the electronic properties of thiol-stabilized Au 25 NCLs, which were found to be strongly quantum confined.…”
Section: Marcus Scheelementioning
confidence: 99%